Removal of heavy metals in a wet detention pond in Reykjavik - Guðbjörg Esther G. Vollertsen 1983- (2010)
Studying wet detention ponds is relevant because they are mainly built to protect salmon rivers. More knowledge is needed on wet detention ponds for Icelandic conditions. The goals of this study are to gather information about the time variability in heavy metal concentration in surface water entering a wet detention pond. In addition, estimate the treatment efficiency for heavy metals in a wet detention pond during different runoff events. Lastly, to evaluate the impact of a detention pond on receiving waters. A wet detention pond in Grafarholt, a suburb of Reykjavik, was monitored during the period of 1st of June 2008 to the 30th of June 2009. Six storm events were chosen and analyzed for a range of heavy metals, suspended solids and particle size. The results of this study are that the heavy metal concentration in water entering the pond was 2 to 7 times lower than heavy metal concentration found in similar ponds in other Nordic countries. Indications of first flush were found in most of the storm events. The particle size distribution was similar to other studies where the size in road runoff was smaller than in pond sediment. The pond had generally high treatment efficiency, around 70-90%, except during one event in the spring. The outflow heavy metal concentration was similar between events, indicating irreducible pollution concentrations. The impact on the receiving water river Úlfarsá was low, concentrations only inclreased by 10 %, and did not change the classification of water quality of receiving waters. Reykjavík Energy Environment and Energy Research Fund and University of Iceland Research Fund